Learning through the memory system: an integral analysis from early childhood (Revista Electrónica Calidad en la Educación Superior, 2025)
This article investigates learning through the memory system, emphasizing the importance of the physical environment as a pedagogical tool that fosters exploration, active participation, and a sense of belonging among students. It also examines the emotional dimension by focusing on the development of interpersonal relationships and the validation of emotions to create atmospheres of confidence and safety within the educational environment. The article approaches this from a holistic perspective on early childhood, an epoch when the educational community serves as a primary participant. The participants’ experiences, gathered through interviews, questionnaires, and observations, enable an analysis of the findings in light of neuroscience. The study yields insights into the value of the overall well-being of the educational community and the creation of learning environments designed to maintain interest and motivation. Therefore, the development of mediation practices consistent with the neurobiological processes of learning, considering the passage of information through sensory, implicit, and explicit memory, is recommended.
Keywords: learning; memory; neuroscience; physiological needs; physical environment; emotional environment; holistic approach